2019
DOI: 10.1590/1982-0216/20192127418
|View full text |Cite
|
Sign up to set email alerts
|

Phonological awareness and early reading and writing abilities in early childhood education: preliminary normative data

Abstract: Objective: to provide preliminary normative data for the Reading and Writing Test by type of school, and normative data for the Phonological Awareness Test by Oral Production for private schools and update their normative data available for public schools, all of which are for children in the final year of early childhood education. Methods: 267 children, in the age range of 5 years, and typical development. Identification Questionnaire for Parents, Phonological Awareness Test by Oral Production and Reading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
0
12
0
9
Order By: Relevance
“…the index to be considered in the Wilcoxon analysis for the comparison of the present data with those of the normative sample. Table 2 includes the mean and SD of the same age sample (five years old), the expected score based on the existing preliminary norms, and the median calculated from the sample in León et al 7 . The median is The comparison between the performance of the children of this study with those of the normative sample inLeón et al 7 , with children from the Southeast Region, revealed significant differences, presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…the index to be considered in the Wilcoxon analysis for the comparison of the present data with those of the normative sample. Table 2 includes the mean and SD of the same age sample (five years old), the expected score based on the existing preliminary norms, and the median calculated from the sample in León et al 7 . The median is The comparison between the performance of the children of this study with those of the normative sample inLeón et al 7 , with children from the Southeast Region, revealed significant differences, presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Such a goal was achieved, and the availability of these performance standards can contribute, from now on, to the usage of the RWT for screening northeastern children. It should be noted that the RWT offered only preliminary norms published only for children of the Southeast Region 6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations